Is BRCA Mutation Testing Cost Effective for Early Stage Breast Cancer Patients Compared to Routine Clinical Surveillance? The Case of an Upper Middle-Income Country in Asia - Lim, Ka Keat; Yoon, Sook Yee; Mohd Taib, Nur Aishah; Shabaruddin, Fatiha Hana; Dahlui, Maznah; Woo, Yin Ling; Thong, Meow Keong; Teo, Soo Hwang; Chaiyakunapruk, Nathorn (Springer Verlag, 2018)
Objective: Previous studies showed that offering BRCA mutation testing to population subgroups at high risk of harbouring the mutation may be cost effective, yet no evidence is available for low- or middle-income countries (LMIC) and in Asia. We estimated the cost effectiveness of BRCA mutation testing in early-stage breast cancer patients with high pre-test probability of harbouring the mutation in Malaysia, an LMIC in Asia. Methods: We developed a decision analytic model to estimate the lifetime costs and quality-adjusted life-years (QALYs) accrued through BRCA mutation testing or routine clinical surveillance (RCS) for a hypothetical cohort of 1000 early-stage breast cancer patients aged 40 years. In the model, patients would decide whether to accept testing and to undertake risk-reducing mastectomy, oophorectomy, tamoxifen, combinations or neither. We calculated the incremental cost-effectiveness ratio (ICER) from the health system perspective. A series of sensitivity analyses were performed. Results: In the base case, testing generated 11.2 QALYs over the lifetime and cost US$4815 per patient whereas RCS generated 11.1 QALYs and cost US$4574 per patient. The ICER of US$2725/QALY was below the cost-effective thresholds. The ICER was sensitive to the discounting of cost, cost of BRCA mutation testing and utility of being risk-free, but the ICERs remained below the thresholds. Probabilistic sensitivity analysis showed that at a threshold of US$9500/QALY, 99.9% of simulations favoured BRCA mutation testing over RCS. Conclusions: Offering BRCA mutation testing to early-stage breast cancer patients identified using a locally-validated risk-assessment tool may be cost effective compared to RCS in Malaysia.